Impact of microorganisms, humidity, and temperature on the enantioselective degradation of imazethapyr in two soils. Issue 7 (19th April 2017) - Wu, Hao; He, Xiaolin; Dong, Huifen; Zhou, Qingyan; Zhang, Yongsong
Abstract: Imazethapyr (IM) is a chiral herbicide composed of an (−)‐R‐enantiomer and an (+)‐S‐enantiomer with differential herbicidal activity. In this study, the effects of microbial organisms, humidity, and temperature on the selective degradation of the (−)‐R‐ and (+)‐S‐enantiomers of IM were determined in silty loam (SL) and clay loam (CL) soil with different pH values. The (−)‐R‐enantiomer of IM was preferentially degraded in two soils under different microorganism, humidity, and temperature conditions. The average half‐lives of R‐IM ranged from 43 to 66.1 days and were significantly shorter ( P < 0.05) than those of S‐IM, which ranged from 51.4 to 79.8 days. The enantiomer fraction (EF = (+)‐S‐enantiomer/((−)‐R‐enantiomer + (+)‐S‐enantiomer)) values were used to describe the enantioselectivity of degradation of IM were >0.5 ( P < 0.05) in two unsterilized soils under different humidity and temperature conditions. The highest EF values were observed at unsterilized CL soil samples under 50% maximum water‐holding capacity (MWHC) and 25 °C environmental conditions. The EF values of the IM enantiomers were significantly higher ( P < 0.05) in CL soils (higher pH = 5.81) and were 0.581 (unsterilized) and 0.575 (50% MWHC; 25 °C) compared with those recorded in SL soil (lower pH = 4.85). In addition, this study revealed that microbial organisms preferentially utilized the more herbicidal active IM enantiomer. Abstract : The enantioselective biodegradation of (R/S:50/50)‐imazethapyr, affected by variation of temperature and maximum water‐holding capacity (MWHC), occurred under a main role of soil microorganisms, resulting more (+)‐S‐imazethapyr stay in two soils.